Meningkatkan keterampilan motorik halus anak usia 5-6 tahun melalui kegiatan kolase dengan media bahan alam - Agysni, Dhea Sasya; Alfarihah, Atiqotul Maula (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
Motor skills are the ability to move parts of the body. Crawling, walking, running, and jumping are examples of motor skills. These skills are categorized into gross motor skills and fine motor skills. Good motor skills are not necessarily acquired by chance alone, but these skills must be acquired through sensory stimulation, teaching, and repeated practice. The focus of this research is only on the development of fine motor skills in children aged 5-6 years, where this skill is more difficult because it requires the ability to coordinate the body with small muscles, as well as training concentration and focus, self-control, and the need for more attention. Various activities can be carried out as an effort by parents and educators to develop fine motor skills, including collage activities. A collage is an activity of pasting and arranging materials systematically on the image surface. The materials used for collage activities in this research are natural in the form of seashells. This research uses quantitative research methods. The research object was Kober Harapan Kita Kalianda, South Lampung with a sample of 30 children aged 5-6 years. The independent variable in this research is collage activities using natural materials as media, while the dependent variable is the fine motor skills of children aged 5-6 years. The results of the t-test calculations in the experimental class are known to be sig, (2-tailed) of 0.00. This sig (2-tailed) value is smaller than 0.05 (5%) which means that Ha is accepted and Ho is rejected. So it can be concluded that collage activities using natural materials as media affect the fine motor skills of children aged 5-6 years in Kober Harapan Kita Kalianda, South Lampung Regency.